(untitled) (Journal of Solar Energy Research Updates, 2025)
This paper aims to explore the electronic and photoelectric properties of two-dimensional type I (straddle) heterojunctions by theoretical calculation, and to provide theoretical support for the design of novel optoelectronic devices. Several ZnIn2S4/CuInS2 two-dimensional type I heterojunctions with different terminations have been systematically investigated by density functional theory (DFT) combined with tight binding approximation. The results show that only two of these structures are stable. In these two stable structures, different chemical bonds and electron transfer directions are formed when different atoms are exposed at the interface. The calculation results of band structures show that both of these structures are two-dimensional type I heterojunctions. The calculation results of effective mass show that they have efficient carrier separation and transport characteristics. These properties indicate that these two heterostructures can be used in high-performance light-emitting devices and photoelectric sensors. This study provides a theoretical basis for the optimal design of new two-dimensional optoelectronic devices.